Use of exchange derivatives and their impact on the value of companies: the case of Chilean non-financial companies - Castillo R., Augusto; Moreno S., David (Estudios de Administración, 2008)
In this paper we analyze the relationship between the use of currency derivatives and the market value of Chilean non financial firms. The results indicate a positive relationship between theamount of derivatives used and the market value of the firm. The use of derivatives allows the firms to reduce their exchange rate exposure, which in turn has a negative impact on the market value of the companies analyzed.